Efficiency of Carbon-Based Electrodes on a Microbial Electrolysis System for the Treatment of Bilge Water - Gatidou, Georgia; Constantinou, Marios; Koutsokeras, Loukas; Vyrides, Ioannis; Constantinides, Georgios (Frontiers in Environmental Science, 2022)
A coupled Microbial Electrolysis Cell (MEC) – Anaerobic Granular Sludge (AGS) system was settled to investigate for the first time the ability of various carbon-based electrodes to enhance biodegradation of real bilge water (BW) and increase methane generation as an emerging technology for converting organic matter into value-added products. Results revealed that the performance of the three types of electrodes named carbon foam (CF), carbon cloth (CC) and three-dimensional graphene foam (3DG), was both time and organic load content dependent during the experimental cycles. Cumulative CH4 generation reached 235 mL in just 13 days after feeding the AGS with 50% of BW and application of 1.0 V at 3DG electrodes, followed by CC electrodes (148.3 mL). CF proved to be more resistant in higher BW concentration showing a sufficient performance of 1 month. However, in the third cycle, the performances of MECs containing 3DG and CC were higher compared to the CF and the control. Over the first cycle, the soluble Chemical Oxygen Demand (sCOD) removal was found to be around 70% to all MECs, and this value was around 10% higher than the control. Among the different Volatile Fatty Acids (VFAs), acetic acid was identified in the highest concentration in the first cycle, whereas propionic acid was detected in the second and third cycles. Microbial profile analysis showed that Methanobacterium and Desulfovibrio had substantially higher abundances in the cathodes than in the suspended anaerobic sludge. An X-ray diffraction (XRD) investigation of the used electrodes pointed out the formation of various crystalline compounds on their surface, which were different for the anode and cathode.